Dictyota adnata Zanardini (Phaeophyceae) - A new record from the Sundarbans mangrove forests, Bangladesh - Islam, Md Ariful; Islam, Md Rashedul; Aziz, Abdul; Liao, Lawrence M (Bangladesh Journal of Botany, 2020)
Samples were collected from Arpangasia and Kholpetua rivers within the Sundarbans in Bangladesh during February to March and December 2018. Among several forms was found a tightly prostrate brown alga occurring on moist parts of mangrove plants and clayey soil. Flattened brownish thalli tightly attached to pneumatophores and lower parts of mangrove trunks, spreading and branching dichotomously, sometimes overlapping and attached by means of unbranched marginal and sub-marginal rhizoids were collected. Distinct marginal sori are well developed in fertile specimens. On the basis of these characters, the sample has been identified as Dictyota adnata Zanardini which is herein reported as a new record for Bangladesh.